2017
DOI: 10.1016/j.cellsig.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

15-Lipoxygenase-1 re-expression in colorectal cancer alters endothelial cell features through enhanced expression of TSP-1 and ICAM-1

Abstract: 15-lipoxygenase-1 (15-LOX-1) oxygenates linoleic acid to 13(S)-hydroxyoctadecadienoic acid (HODE). The enzyme is widely suppressed in different cancers and its re-expression has tumor suppressive effects. 15-LOX-1 has been shown to inhibit neoangiogenesis in colorectal cancer (CRC); in the present study we confirm this phenomenon and describe the mechanistic basis. We show that re-expression of 15-LOX-1 in CRC cell lines resulted in decreased transcriptional activity of HIF1α and reduced the expression and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Since 15-LOX-1 was downregulated in doxorubicin-resistant cells compared with their drug-sensitive parental cells, we next examined whether ectopic overexpression of 15-LOX-1 affected drug resistance. We used a mammalian overexpression vector (pcDNA3.1[−]-ALOX15) that was previously designed and confirmed to produce a functional 15-LOX-1 protein (Cimen et al, 2009;Tuncer et al, 2017).…”
Section: Overexpression Of 15-lox-1 Resensitized Mcf7 Dox and Hela mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 15-LOX-1 was downregulated in doxorubicin-resistant cells compared with their drug-sensitive parental cells, we next examined whether ectopic overexpression of 15-LOX-1 affected drug resistance. We used a mammalian overexpression vector (pcDNA3.1[−]-ALOX15) that was previously designed and confirmed to produce a functional 15-LOX-1 protein (Cimen et al, 2009;Tuncer et al, 2017).…”
Section: Overexpression Of 15-lox-1 Resensitized Mcf7 Dox and Hela mentioning
confidence: 99%
“…Moreover, 15-LOX-1 has also been linked to the regulation of necrosis via regulating intracellular redox state by cooperating with 12-lipoxygenase (Berghe, Linkermann, Jouan-Lanhouet, Walczak, & Vandenabeele, 2014). 15-LOX-1 has been demonstrated to be associated with tumorigenesis in different tissue types, and was reported to be mostly downregulated in cancer cells (Moussalli et al, 2011;Tian et al, 2017;Tuncer et al, 2017). In breast cancer, immunohistochemistry as well as gene expression studies have indicated a downregulation of ALOX15 expression in the tumor tissues compared to normal cells (Jiang, Watkins, Douglas-Jones, & Mansel, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Complicating the story even further, recently, 15‐LOX‐1 over‐expression in PC‐3 cells was shown to reduce angiogenesis through a ubiquitin‐mediated enhanced degradation of HIF‐1α and a consequent lower expression of VEGF‐A mRNA . Supporting the anti‐angiogenic role of 15‐LOX‐1, we have recently shown that re‐expression of 15‐LOX‐1 in HCT‐116 and SW‐480 CRC cell lines and LNCaP prostate cancer cells reduced the expression and secretion of VEGF‐A in both normoxic and hypoxic conditions and CM from these cells decreased endothelial cell motility and tube formation . Moreover, 15‐LOX‐1 CM treated mouse aortic rings showed significantly less sprouting with a more organized (less chaotic) structure of vascular network .…”
Section: ‐Lox‐1 In the Tumour Microenvironmentmentioning
confidence: 64%
“…Moreover, 15‐LOX‐1 CM treated mouse aortic rings showed significantly less sprouting with a more organized (less chaotic) structure of vascular network . Mechanistically, endothelial cells treated with CM from 15‐LOX‐1 overexpressing CRC cell lines showed enhanced expression of Thrombospondin‐1 (TSP‐1), a matrix glycoprotein known to strongly inhibit neovascularization . TSP‐1 interacts with a vast number of different proteins, many of which play important roles in extracellular matrix remodelling, interactions between cells and the cell and extracellular matrix, motility and vascular normalization .…”
Section: ‐Lox‐1 In the Tumour Microenvironmentmentioning
confidence: 99%
“…Produced by endothelial cells, it would behave like an anti-inflammatory metabolite as a ligand for PPAR α and γ. Its synthesis led to reduce angiogenesis in colon and prostate cancer 44 or enhanced the axonal outgrowth in primary cortical neurons during development of rats in a gender-dependent manner 45 . Altogether, these works underline the pleiotropic dimension of action of HODEs.…”
Section: Discussionmentioning
confidence: 99%